The performing body: kinesic codes in wole Soyinka’s drama - Figueiredo, Rosa (2014)
The powerful presence of the theatricalised post-colonial body, suggests that foregrounding corporeality can be a highly positive, active strategy for staging traditional enactments such as ritual. As a culturally coded activity, dance, for example, has a number of important functions in drama: not only does it concentrate the audience's gaze on the performing body, but it also draws attention to proxemic relations between characters, spectators, and features of the set. Splitting the focus from other sorts of proxemic and kinesic codes, dance renegotiates dramatic action and dramatic activity, reinforcing the actor's corporeality, particularly when it is culturally laden. Wole Soyinka's plays, our raw material, abound in bodies and voices, in spectacle and movement and colour; in multiple settings, flashbacks and dramatic re-enactments.